The Effect Of Promotions, Service Qualities And Store Display Products Buyers Decisions At Hypermart Bengkulu Indah Mall - Agilia Putri Ayu Dewanti; Yun Fitriano; Dennis Rydarto Tambunan (Penerbit Jurnal Indonesia, 2024)
This study aims to find out whether the effect of promotions, service qualities and store display products on buyers' decisions at Hypermart Bengkulu Indah Mall. This research used a questionnaire method with a total of 100 respondents from Hypermart Bengkulu Indah Mall consumers. The research results show that Store Display product X3 has a greater effect on buyers’ decisions with a regression value of 0.506, while Promotion X1 has a value of 0.198 and Service Quality. The results of this research also show that multiple linear regression Y=-877 +0.198X1+0.328X2+0.506X3+1.117. The results of the Promotion Test The results of the Service Quality Test Store Display Product X3 test results with a significance value of 0.000 < 0.05, meaning that Ha is accepted and Ho is rejected. The research results show that promotion, service quality and product store displays have an influence on buyers' decisions at Hypermart Bengkulu Indah Mall, especially on the product store display variable.